Scorpion sheds 'tail' to escape: consequences and implications of autotomy in scorpions (Buthidae: Ananteris) - Mattoni, Camilo Ivan (2015)
Autotomy, the voluntary shedding or detachment of a body part at a determined cleavage plane, is a common anti-predation defense mechanism in several animal taxa, including arthropods. Among arachnids, autotomy has been observed in harvestmen, mites, and spiders, always involving the loss of legs. Autotomy of the opisthosoma (abdomen) was recently reported in a single species of the Neotropical buthid scorpion genus Ananteris Thorell, 1891, but few details were revealed. Based on observations in the field and laboratory, examination of material in museum collections, and scanning electron microscopy, we document autotomy of the metasoma (the hind part of the opisthosoma, or ?tail?) in fourteen species of Ananteris. Autotomy is more common in males than females, and has not been observed in juveniles. When the scorpion is held by the metasoma, it is voluntarily severed at the joints between metasomal segments I and II, II and III, or III and IV, allowing the scorpion to escape. After detachment, the severed metasoma moves (twitches) automatically, much like the severed tail of a lizard or the severed leg of a spider, and reacts to contact, even attempting to sting. The severed surface heals rapidly, scar tissue forming in five days. The lost metasomal segments and telson cannot be regenerated. Autotomy of the metasoma and telson results in permanent loss of the posterior part of the scorpion?s digestive system (the anus is situated posteriorly on metasomal segment V) and the ability to inject venom by stinging. After autotomy, scorpions do not defecate and can only capture small prey items. However, males can survive and mate successfully for up to eight months in the laboratory. In spite of diminished predation ability after autotomy, survival allows males to reproduce. Autotomy in Ananteris therefore appears to be an effective, adaptive, anti-predation escape mechanism.